A Co-CRISPR Strategy for Efficient Genome Editing in Caenorhabditis elegans. Issue 4 (1st August 2014) - Kim, Heesun; Ishidate, Takao; Ghanta, Krishna S; Seth, Meetu; Conte, Darryl; Shirayama, Masaki; Mello, Craig C
Abstract: Genome editing based on CRISPR (clustered regularly interspaced short palindromic repeats)-associated nuclease (Cas9) has been successfully applied in dozens of diverse plant and animal species, including the nematode Caenorhabditis elegans . The rapid life cycle and easy access to the ovary by micro-injection make C. elegans an ideal organism both for applying CRISPR-Cas9 genome editing technology and for optimizing genome-editing protocols. Here we report efficient and straightforward CRISPR-Cas9 genome-editing methods for C . elegans, including a Co-CRISPR strategy that facilitates detection of genome-editing events. We describe methods for detecting homologous recombination (HR) events, including direct screening methods as well as new selection/counterselection strategies. Our findings reveal a surprisingly high frequency of HR-mediated gene conversion, making it possible to rapidly and precisely edit the C. elegans genome both with and without the use of co-inserted marker genes.